2012
DOI: 10.1002/ijc.27629
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of syndecan‐1 by microRNA miR‐10b promotes breast cancer cell motility and invasiveness via a Rho‐GTPase‐ and E‐cadherin‐dependent mechanism

Abstract: microRNAs are small endogenous noncoding RNAs, which post-transcriptionally regulate gene expression. In breast cancer, overexpression of the transmembrane heparan sulfate proteoglycan syndecan-1, a predicted target of the oncomiR miR-10b, correlates with poor clinical outcome. To investigate the potential functional relationship of miR-10b and syndecan-1, MDA-MB-231 and MCF-7 breast cancer cells were transiently transfected with pre-miR-10b, syndecan-1 siRNA or control reagents, respectively. Altered cell beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
158
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 46 publications
(107 reference statements)
16
158
3
3
Order By: Relevance
“…Tumor invasion and metastasis is a complex and multistep process: miR-10b may play different roles via different targets [18,22,24,25]. Previous studies indicated that miR-10b restrained Tiam1 by translational inhibition, in which the 3 0 UTR miR-10b-binding site is crucial [26].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor invasion and metastasis is a complex and multistep process: miR-10b may play different roles via different targets [18,22,24,25]. Previous studies indicated that miR-10b restrained Tiam1 by translational inhibition, in which the 3 0 UTR miR-10b-binding site is crucial [26].…”
Section: Discussionmentioning
confidence: 99%
“…As we also observed syndecan-1-dependent wound closure in the presence of mitomycin blocking cell proliferation, we conclude that syndecan-1 is critical for migration of cells into the wounded area. Several signaling pathways that are implicated in cell proliferation and migration including p38, Akt, Rho GTPase and FAK are modulated by knockdown or overexpression of syndecan-1 [20,40,41]. However, the effects appear to be cell-type dependent.…”
Section: Discussionmentioning
confidence: 98%
“…Other potentially critical factors that may be relevant in TNBC include the interplay between EGFR and insulin-like growth factor receptor signaling systems and production of cell surface effectors such as the subclass of heparin sulfate proteoglycans known as syndecans (52)(53)(54)(55)(56). Understanding how these different factors are integrated to drive metastatic progression will provide the Somewhat surprisingly, our data also appear to exclude a role for autocrine IL-6 because EMT programs fail to diminish the ability of NME cells to activate STAT3 in response to exogenous IL-6.…”
Section: Figure 4 Emt Inhibits Egfr-dependent Stat3 Signalingmentioning
confidence: 99%